Risk reduction through urban spatial resilience: A theoretical framework. Issue 4 (21st April 2021) - Lu, Yuwen; Zhai, Guofang; Zhou, Shutian; Shi, Yijun
Abstract: Resilience provides an adaptive approach for dealing with environmental change, natural risks and public health emergencies. Urban spatial resilience is an interpretation of resilience in the spatial dimension. However, studies on urban spatial resilience and the relationship between resilience and urban space are limited. This study tries to understand urban spatial systems and to establish an urban spatial resilience theoretical framework by integrating resilience into urban spaces to reduce urban risks. This article describes urban spatial resilience by identifying a set of urban spatial factors that may affect resilience and by linking spatial elements and resilience characteristics. The theoretical framework of urban spatial resilience has been divided into five dimensions here, urban spatial scale resilience, urban spatial structure resilience, urban spatial form resilience, urban spatial function resilience, and urban spatial network resilience. This study considers the advantages of spatial resilience from landscape ecology and urban resilience from urban studies. As a supplement to existing resilience research, this study provides a new perspective on improving the resilience of urban spaces and reduce urban risks, and guides spatial planning practitioners.